Occurrence of imagery and its link with early memories in agoraphobia. - Day, S; Holmes, E; Hackmann, A (2004)
Recent cognitive models suggest that mental imagery can help us understand the maintenance of anxiety disorders (e.g., de Silva, 1986; Hackmann, Surawy, and Clark, 1998). However, imagery is relatively unexplored within agoraphobia. Such images are also thought to be useful in uncovering memories that occurred around the onset of a disorder (Hackmann, Clark, and McManus, 2000). A total of 20 patients with agoraphobia and 20 matched controls took part in this investigation. Participants described any recurrent images they experienced in agoraphobic situations, and also any associated memories. All patients with agoraphobia (but no control participants) reported having distinct recurrent images in "agoraphobic situations". Most images involved several sensory modalities and in the majority of cases appeared to be linked with unpleasant memories of events experienced many years previously. While these exploratory findings require replication, potential treatment implications are discussed.